2011
DOI: 10.1111/j.1439-0531.2011.01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in the Concentrations of Prostaglandin F2α (PGF) and Cortisol in Uterine and Ovarian Venous Blood During PGF‐induced Luteolysis in Cows

Abstract: Prostaglandin F2α (PGF) is considered to be the main luteolysin in cattle. We have previously demonstrated that cortisol (Cr) suppresses PGF production in non-pregnant bovine endometrium. This study was carried out to test whether exogenous PGF increases ovarian and/or uterine PGF production and to determine the temporal relationship between PGF and Cr in ovarian and uterine circulations during PGF-induced luteolysis in cows. Catheters were inserted into the ovarian vein (OV), uterine vein (UV) and jugular vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
(47 reference statements)
4
12
0
Order By: Relevance
“…Recent in vivo studies (Shrestha et al. 2010; Duong et al. 2011b) have shown that Cr plays a role in regulating PGF secretion in the bovine uterus during PGF‐induced luteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent in vivo studies (Shrestha et al. 2010; Duong et al. 2011b) have shown that Cr plays a role in regulating PGF secretion in the bovine uterus during PGF‐induced luteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…2010). Furthermore, a concomitant elevation of uterine PGF and Cr concentrations was observed after an analogue of PGF injection and then concentration of PGF decreased after Cr reached its highest levels (Duong et al. 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for the initiation of bovine luteal regression, the pulsatile character of PGF 2α is much more important and plays a mandatory role rather than its absolute levels [56,57]. Furthermore, cortisol has been suggested to act in reducing the high levels of uterine PGF and to be one of the factors responsible for the generation of PGF 2α pulses in vivo in cattle [58]. Cortisol is well-known as a local regulator/modulator of PG secretion [8].…”
mentioning
confidence: 99%